The Taj Mahal as a heritage of Islamic architecture of the Mughal dynasty - bilge dhaifa (Pascasarjana UIN Raden Mas Said Surakarta, 2025)
This article aims to examine and understand the Taj Mahal as an Islamic architectural heritage that represents the grandeur, spirituality, and aesthetic values of the Mughal Dynasty. This study was conducted to explore how Islamic cultural elements can blend with local Indian traditions through monumental architectural works. Through a descriptive-historical approach, this paper highlights the process of acculturation that gave birth to the distinctive Mughal architectural style, which combines Persian, Turkish, Central Asian, and Indian influences. The main focus of this study is to reveal the symbolic meaning behind the design of the Taj Mahal, from the Charbagh garden concept and the use of white marble to the Al-Qur'an calligraphy that adorns the walls of the building. This study also aims to show that the Taj Mahal not only serves as a monument to love, but also as a means of legitimizing power and expressing the high civilization of Islam. By understanding its historical, spiritual, and artistic aspects, it is hoped that readers will see the Taj Mahal as proof that Islamic architecture can be a medium for da'wah, art, and reflection on universal human values.